Mastering automotive challenges [ - Gottschalk, Bernd , 1943-; Kalmbach, Ralf (Kogan Page, 2007)
Charts the growth and achievement of dominance of one of the world's most important global industries. This book features contributions from Roland Berger Strategy Consultants and the chairman of the